Postponed Olympic Dreams: High-Performance Athletes’ Experience in Coping with Postponed Tokyo 2020 Olympic Games - Hong Hee Jung; Botwina Grzegorz (Physical Culture and Sport: Studies and Research, 2025)
The study aims to understand how high-performance athletes preparing for the Tokyo 2020 Olympic Games coped with challenges caused by the International Olympic Committee’s (IOC) decision to postpone the Olympics as well as the COVID-19 pandemic by analysing varying experiences across different social contexts. It also investigates the organizational support in place to assist them during this unprecedented period, from sports governing bodies such as NOC’s and NGB’s. Semi-structured interviews were conducted with sixteen high performance athletes from Poland, Portugal, and South Korea, who had either qualified for Tokyo 2020 or were due to complete their qualification events. Thematic analysis was applied to analyze the data collected from these interviews, providing insights into the athletes’ experiences and coping strategies as well as organizational support they have received. Athletes reported utilizing internal resources such as goal setting, showing high resilience. They also relied on external resources, including organizational and social support. Support from sport governing bodies varied by country. Regardless, athletes highlighted the need for organizational, informational, psychological and financial support to address challenges and prepare for the postponed Olympics. The findings suggest sport governing bodies should maintain ongoing and up-to-date communication with athletes and conduct regular wellbeing checks to address potential concerns. By examining the immediate and practical impacts of the Tokyo 2020 Olympics postponement and the COVID-19 pandemic on high-performance athletes, this study offers empirical evidence on their perceived needs. These findings highlight the need for structured support initiatives from sport governing bodies and organizations as well as the proactive development of targeted support strategies for future sports mega events. Such measures will facilitate that athletes are better prepared and adequately supported during times of crisis.